Adaptasi Burung Kasuari Sebagai Sumber Ide Pembelajaran Make Up Fantasi Mixed Media - Athaya, Jasmine; Tresna, Pipin; Ruhidawati, Cucu (LPPM Institut Pendidikan Nusantara Global, 2024)
The cassowary consists of various feather colors, rough and shiny black feathers on its body, blue on the neck and scalp, and red wattle on the throat. The beauty of these colors can be adapted into a source of ideas in making fantasy makeup with mixed media techniques. Fantasy makeup is an art that combines creativity, imagination, and makeup techniques to create a certain imaginary form. The creation of fantasy makeup can use various techniques, one of them is mixed media. Mixed media makeup usually involves two or more media combined to produce a work of art in the form of a new image that is completely different from the original form. The purpose of this study is to represent the beauty of the Indonesian archipelago by selecting the magnificent Papuan cassowary birds as a source of ideas for fantasy makeup with mixed media techniques. The research used the R&D method with the ADDIE development model. 1) Analysis: analyzing the source of ideas that inspire the making of products, 2) Design: making a product moodboard, 3) Development: product design in the form of makeup and outfit design, 4) Implementation: making research products in the form of fantasy makeup with cassowary bird idea sources, 5) Evaluation: evaluating the results of products that have been made, namely makeup analysis in the form of analysis of visual elements and design principles. The research produced a product in the form of mixed media fantasy makeup with the source idea of bird adaptation.